2021
DOI: 10.3390/ijms23010191
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Extracellular Vesicles as Therapeutic Nanocarriers

Abstract: Mammalian exosomes have emerged as a promising class of functional materials, inspiring novel applications as therapeutic vehicles and nutraceutical compounds. Despite this, their immunogenicity has been an issue of controversy within the scientific community. Although, exosome-like vesicles, innately formed in plants and inherent to eukaryotic cell-derived vesicles, could soothe most of the concerns, they are notably underutilized as therapeutic modalities. This review highlights all efforts published so far,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 40 publications
(129 reference statements)
0
68
0
Order By: Relevance
“…Recently, growing evidence has suggested possible therapeutic applications for nanoparticles derived from edible plants [ 13 , 14 , 15 ], especially when administered orally to induce immunomodulation. However, their entry pathways and activities are still debated.…”
Section: Plant-derived Evs In Cross-kingdom Delivery—truth or Imagina...mentioning
confidence: 99%
“…Recently, growing evidence has suggested possible therapeutic applications for nanoparticles derived from edible plants [ 13 , 14 , 15 ], especially when administered orally to induce immunomodulation. However, their entry pathways and activities are still debated.…”
Section: Plant-derived Evs In Cross-kingdom Delivery—truth or Imagina...mentioning
confidence: 99%
“…(2) EVs-based therapy is another application of EVs in medicine. As mentioned above, many researchers have shown that EVs from various plants have anticancer or regenerative properties [ 127 , 128 ]. For example, EVs from different plants are cytotoxic and anti-proliferative for many tumor cells [ 44 ].…”
Section: Advantages and Challengesmentioning
confidence: 99%
“…Plant-derived exosome-like nanoparticles (ELNs) have been shown to also prevent and treat a variety of diseases, with functions closely related to the plant of origin ( Teng et al, 2018 ; Cong et al, 2022 ). ELNs have lipid membrane structures that can also be used as natural or engineered carriers for drug loading and delivery ( Karamanidou & Tsouknidas, 2021 ). Moreover, ELNs are cost-effective and easy to obtain, and have great potential for development and application.…”
Section: Exosomes As Targets For the Treatment Of Cardiac Fibrosismentioning
confidence: 99%